Digeneans in Trachemys callirrostris callirostris and Podocnemis lewyana (Testudinata) from the Magdalena River, Colombia: description of Pseudonematophila n. gen. and amendment of Nematophila Travassos, 1934 (Cladorchiidae: Schizamphistominae) - Lenis, Carolina; Vélez, Imelda (Zootaxa, 2011)
A survey of the parasites associated with the nesting freshwater turtles Podocnemis lewyana and Trachemys callirostris callirostris revealed the presence of seven Digenea species. Pseudonematophila n. gen. is described from the stomach of P. lewyana. The new genus is distinguished from other Schizamphistominae because it possesses a genital sucker and numerous tegumental papillae from the posterior level of the genital sucker to the posterior end of the body, which had not been described before for this subfamily. Nematophila ovalis Cordero & Vogelsang, 1940 is transferred to Pseudonematophila n. gen. as P. ovalis n. gen. n. comb, based on morphological characteristics. The genus Nematophila Travassos, 1934 is emended by the inclusion of Allassostoma venezuelensis and Paramphistomum argentinum described by Cordero & Vogelsang in 1940. Both species are redescribed based on Colombian specimens, and the first key for the genus is provided. Telorchis hagmanni Lent & Freitas, 1937 is redescribed from Colombian specimens, and Telorchis corti, Heronimus mollis and Neodeuterobaris pritchadae are reported. Prevalence, mean intensity, and mean abundance values are estimated for all species. Host feeding habits and behavior are considered the main factors determining the taxonomic composition founded in these turtles species.